2013
DOI: 10.18052/www.scipress.com/ilcpa.23.12
|View full text |Cite
|
Sign up to set email alerts
|

Change in Energy and Entropy of the Non-Spinning Black Holes

Abstract: In the present paper, we have derived an expression for change in entropy of non-spinning black holes on the basis of formula ( BH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Mahto, D., Kumari, A. and Singh, K.M. have shown that there is no any change in the energy and entropy of black holes having zero spin and leading the second laws of thermodynamics ( 0 dS ≥ ) [5]. Mahto, D. and Kumari, A. proposed a model for the change in entropy of spinning black holes due to change in mass using first law of black hole mechanics for unit spinning parameter and angular momentum and also calculated their values for different spinning black holes in XRBs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mahto, D., Kumari, A. and Singh, K.M. have shown that there is no any change in the energy and entropy of black holes having zero spin and leading the second laws of thermodynamics ( 0 dS ≥ ) [5]. Mahto, D. and Kumari, A. proposed a model for the change in entropy of spinning black holes due to change in mass using first law of black hole mechanics for unit spinning parameter and angular momentum and also calculated their values for different spinning black holes in XRBs [6].…”
Section: Introductionmentioning
confidence: 99%